Quality Control Analysis to Reduce the Number of Defects in DTY Yarn Products Using the Six Sigma (DMAIC) Method at PT. XYZ - Muhammad Ihsan; Althaaf Fawwaz Wanna; Indra Gumelar (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
This study aims to identify the dominant types of defects, analyze the root causes of product defects, and propose quality improvement recommendations to reduce the defect rate of DTY products. The research employed the Six Sigma method using the Define, Measure, Analyze, Improve, and Control (DMAIC) approach integrated with Failure Mode and Effect Analysis (FMEA). In the Define phase, the production process was identified through a SIPOC diagram and the determination of Critical to Quality (CTQ) characteristics. The Measure phase included the calculation of defect proportions, control charts, Defects per Million Opportunities (DPMO), sigma level, and process capability. The Analyze phase utilized Pareto diagrams, Fishbone diagrams, and FMEA to identify the root causes of defects and determine improvement priorities based on the Risk Priority Number (RPN). The Improve phase generated improvement recommendations using the 5W+1H approach, while the Control phase provided recommendations to sustain the implemented improvements. The results showed that during the January–December 2025 period, total production reached 3,793,630 kg, with 116,148 kg of defective products, resulting in a defect rate of 3.06%, which exceeded the company's maximum tolerance limit of 1%. Pareto analysis identified four dominant defect types: Dyeing Reject (31.73%), Damaged (23.76%), DP Handling (23.25%), and Cutting (20.39%). The FMEA results indicated that the highest-priority risks were Dyeing Reject caused by misthreading and Cutting caused by material property problems, both with an RPN value of 300. The proposed improvements focus on enhancing operator competence through training, ensuring consistent implementation of Standard Operating Procedures (SOPs), performing preventive machine maintenance, strengthening raw material quality control, improving workplace cleanliness, and enhancing production process supervision. The implementation of these recommendations is expected to reduce product defects, improve process capability, and support the achievement of product quality standards established by the company.